Intestinal parasitic infections among type-2 diabetics seeking healthcare in Sanaa city, Yemen - Rashad Abdul-Ghani; Kwkab A. R. Al-Brhami; Abdulslam K. M. Baalawi; Amani A. M. Khodeif; Asma'a A. Y. Al-Wshali; Azhar H. Y. Abo-Hadi; Eshtiaq H. S. Al-Saigel; Hanan A. A. Al-Gomaei; Hani M. A. Al-Gatta; Maroof H. M. Abdo; Muhammad S. A. Al-Musheriae; Roqia S. S. Al-Mohiya; et al. (Polish Parasitological Society, 2022)
Intestinal parasitic infections (IPIs) are common in developing countries, particularly in countries witnessing conflicts and humanitarian crises like Yemen. Type-2 diabetics are among the population categories most vulnerable to a variety of infections, including IPIs. Therefore, this study determined the prevalence and risk factors associated with IPIs among Yemeni type-2 diabetics in Sanaa city. This hospital-based, cross-sectional study recruited 389 type-2 diabetics seeking healthcare in Sanaa from December 2019 to February 2020. Sociodemographic data and risk factors were collected from interviewed participants using a structured questionnaire. Stool samples were collected and examined for parasites using standard techniques. The association of sociodemographic characteristics and risk factors with IPIs was tested using univariate analysis, and a multivariable logistic regression model was developed to identify the independent predictors of IPIs at a significance level of <0.05. The overall prevalence of IPIs among diabetics was 38.6%. Entamoeba histolytica/dispar (30.3%) was the most frequent parasite, followed by Cryptosporidium species (8.2%). The significant independent predictors of IPIs were duration of diabetes mellitus > 10 years (AOR = 1.6; 95% CI: 1.102.47, P = 0.029), eating unwashed vegetables/fruits (AOR = 3.2; 95% CI: 1.446.92, P = 0.004) and not practicing handwashing before meals (AOR = 2.4; 95% CI: 1.105.48, P = 0.035). Over one-third of type-2 diabetics seeking healthcare in Sanaa city are infected with one or more IPIs, predominantly with E. histolytica/dispar, followed by Cryptosporidium species. Such infections cannot be predicted from the sociodemographic characteristics of diabetics. Nevertheless, prolonged duration of diabetes mellitus, eating unwashed vegetables/fruits and not practicing handwashing before meals are independent predictors of IPIs among type-2 diabetics. Large-scale studies are recommended for IPIs among type-2 diabetics with and without gastrointestinal complaints, preferably in comparison to non-diabetics.